Analysis of Fisbein Multiattribute on Product of Chocolate Sandwich Cookies - Ujang Sumarwan (Media Gizi dan Keluarga, 2000)
The purpose of this study was to examine the consumers’ attitudes toward chocolate sandwich biscuits of two different brands. The organoleptic tests were conducted for collecting the data from 85 respondents who were purposively selected in Bogor. The respondents were asked to evaluate six atributes of the products on a 5 point scale, based on Multiatribute Fishbein of the Attitude-Toward-Object Model. The results showed that the six atributes of the product were evaluated to be important. The Fishbein attitude score for OREO brand was higher than that of RODEO brand, indicating that respondents were more favorable toward (more positive attitude) OREO than RODEO.Keywords: consumer, attitudes